MEMBANGUN WEBSITE SEBAGAI MEDIA RESERVASI OBJECT WISATA MENGGUNAKAN METODE APRORI - Eddi Kurniyadi; Agus Sujarwadi (LPPM STMIK Lombok, 2018)
With the growing of information technology and internet. The Lombok Travel is one of the few journeys in the development of the system. Currently, there are also manual transactions. In addition, the packages for tourist destinations are usually set based on the packages that have been made the trip, but also the ordering system that is online in order for members in ordering transactions. Aprioriic method to display the most popular tour packages or tour packages most in the message by previous customers. For the application of this method will be made based website system. The results of this study are Applications that use Apriori Method to display the most popular tour packages, tour packages, travel destinations, price packages, package messages and members can directly place an order package on a system that can be accessed online.